Preparation and Antibacterial Activity of Mixed Ligand Complexes of Co(II), Ni(II), Cu(II) and Cd(II) Derived from 1-Phenylazo-2-naphthol and Salicylaldehyde - S. A. I. Sharif; A. N. El-Tajoury; A. A. Elamari (E-Journal of Chemistry)
The mixed ligand complexes of Co(II), Ni(II), Cu(II) and Cd(II) have been synthesized by using 1-phenylazo-2-naphthol as primary ligand and salicylaldehyde as secondary ligand. All the prepared complexes were identified and confirmed by elemental analyses (C, H and N), molar conductance measurements, infrared, electronic absorption and electron paramagnetic resonance. The elemental analysis data suggest that the stoichiometry of the complexes to be 1:1:1[M: L1: L2] ratio. The molar conductance measurements of the complexes indicate their non-electrolytic nature. The infrared spectral data showed the coordination sites of the free ligand with the central metal ion. The electronic absorption spectral data revealed the existence of an octahedral geometry for Co(II) and Cd(II) complexes and a square planar geometry for Ni(II) and Cu(II) complexes. The electron paramagnetic resonance spectra of the Co(II) and Cu(II) complexes showed the existence a paramagnetic phenomenon and supported their geometrical structures which confirmed by the electronic absorption spectra. The ligands and mixed ligand complexes have been tested on antibacterial activity against three strains of pathogenic bacteria such as Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa